Regresi Data Panel untuk Mengetahui Faktor-Faktor yang Mempengaruhi PDRB di Provinsi DIY Tahun 2011-2015 - Dea Aulia Nandita; Lalu Bayu Alamsyah; Enggar Prima Jati; Edy Widodo (Universitas Sebelas Maret, 2019)
Population growth can encourage and hinder economic growth. This study aims to analyze the factors that influence gross domestic product (GDP) in Daerah Istimewa Yogyakarta (DIY) using panel data regression. This study uses three independent variables, namely number of population, number of poor population, and investment, while the dependent variable is GDP. We use secondary data obtained from Badan Pusat Statistik (BPS). The results obtained from the regression analysis of the data series time panel are generalized least square (GLS), while for the cross section data panel shows the REM model is more suitable than PLS and FEM. Based on the validity test of the influence or t-test, the variable that shows significant to the economic rate which is categorized as GRDP in the Daerah Istimewa Yogyakarta in 2011-2015 is the variable Total population and Investment which has a positive relationship.Keywords : economic growth rate, panel data regression, gross regional domestic product